Analisis Peran Pendapatan Non-Pendidikan dalam Mendukung Keberlanjutan Sumber daya Keuangan pada Politeknik Negeri Semarang (Polines) - Masula, Fariham; Zagladi, Arief Noviarakhman (Universitas Proklamasi 45, 2025)
This study aims to analyze the role of non-educational revenue in supporting the financial sustainability of Politeknik Negeri Semarang (Polines). Using a qualitative research method with a document analysis approach, this research examines Polines' revenue realization from 2020 to 2023. The findings reveal that non-educational revenue is pivotal in enhancing Polines’ financial flexibility and independence. Nevertheless, Polines continues to face challenges, including reliance on the State Budget (APBN) and underutilization of its research and innovation potential. The study recommends strategies for revenue diversification, strengthening governance, and optimizing innovation to enhance Polines’ financial sustainability. These strategies emphasize the concept of an entrepreneurial university and utilize Valuable, Rare, Inimitable, and Organized (VRIO).